The effect of osmotic stress towards the expressions of thiamine biosynthesis genes (THIC & THI1/THI4) in oil palm (Elaeis guineensis) - Wong, Sook Yee (2015)
Thiamine or vitamin B1 composes of a pyrimidine moiety and a thiazole moiety. Thiamine pyrophosphate (TPP), the active form of thiamine, acts as a cofactor for various major enzymes for example transketolase (TK), α-ketoglutarate dehydrogenase (KGDH) and pyruvate dehydrogenase (PDH). In this study, THIC and THI1/THI4 gene transcripts, the first two enzymes in thiamine biosynthesis pathway were identified and amplified in oil palm. Primers were designed based on sequence comparison of the genes from Arabidopsis thaliana, Zea mays, Oryza sativa and Alnus glutinosa. The responses of oil palm through the expression profiles of thiamine biosynthesis genes (THIC and THI1/THI4), in response to polyethylene glycol (PEG) which induce osmotic stress were examined. This is due to the suggestion that TPP has another important role, which is protecting plants against abiotic and biotic stresses. The expression of gene transcripts were detected using reverse transcriptase polymerase chain reaction (RT-PCR) and from the 8 sets of primers designed, primer 3 (F3) for THIC gene and primer 8 (F8) for THI1/THI4 successfully amplified the transcripts. The results showed that THIC gene expression increases (200% of increase in treated plant compared to non-treated plant) in the presence of 1% PEG. The expression of THI1/THI4 gene caused by stress showed similar results to that of THIC gene but in accumulation of no more than 2.0-fold (100% of increase in treated plant compared to non-treated plant). The results agreed with the suggestion that thiamine may play important function in plant defence against stresses as these findings may lead to an overexpression of thiamine in general.